Functional implications of Bone Morphogenetic Protein 10 (BMP10) expression in pathological hearts - Piotrowska, Izabela; Justus Liebig University Giessen (My University, 2006)
BMP10 is a cardiac specific member of the TGF beta superfamily and the expression of this cytokine is limited to the right atrium of the healthy heart. In the work presented here, I attempted to unveil the function of BMP10 in the pathological adult heart. RESULTS: 1. During embryonic heart development BMP10 expression was found in the trabeculated myocardial layer and BMP10 protein was observed additionally in the outflow tract, the compacted heart wall and the epicardial layer. 2. BMP10 in the healthy adult heart is expressed in the right atrium and after secretion binds to the membrane of both atrial cardiomyocytes and interstitial cells. Moreover, expression and binding of this protein was observed in the tricuspid valve and cells adjacent to the arteries in the upper atrial area of the heart. 3. The murine models used in this study represent the dilated and hypertrophic type of cardiomyopathy and exhibit different degrees of cardiac dysfunction characterized by changes in myocardial volume and reduced ejection fraction. Interstitial and replacement fibrosis, cardiomyocyte hypertrophy, myofiber disarray and cell death in respect to necrosis and apoptosis were detected but the degree of structural changes was different in all models. The number of apoptotic or necrotic cells was very low. 4. In diseased hearts two types of qualitative BMP10 distribution changes were found. The subcellular localization of BMP10 in cells of the right atrium was changed. In addition, BMP10 was re-expressed in ventricular cells. 5. In Desmin knock-out and in doxorubicin induced dilated cardiomyopathy upregulation of the BMP10 expression was found, while quantification of BMP10 in MnSOD heterozygous and isoproterenol treated mouse heart revealed its downregulation. These variations in BMP10 quantity were monitored at the RNA and protein level. The number of BMP10 positive cells in the ventricles of pathological hearts is low, and therefore quantitative changes represent most probably the deregulation of BMP10 expression in the right atrium. 6. Ventricular cells ectopically expressing BMP10 in pathological hearts are Sca1pos. and show signs of proliferation. Characterization of the ventricular BMP10pos. cells revealed that they constitute a heterogeneous population of cells often expressing endothelial and smooth muscle cell markers, but never cardiomyocyte specific genes. BMP10 is expressed, however, by embryonic and atrial cardiomyocytes. 7. BMP10 effects are dependent on the differentially expressed receptors in various cell lines. The effect of BMP10 in C2C12 cells is limited to the induction of osteoblast differentiation. In contrast, BMP10 induced multipotent mesenchymal 10T1/2 embryonic fibroblasts, adult bone marrow mesenchymal stem cells and in non-cardiomyocytes isolated from the adult mouse heart to express smooth muscle, endothelial and pericyte markers. Moreover, cells expressing these markers are able to form 3D tube-like structures indicating a possible role of BMP10 in angiogenesis. CONCLUSION:On the basis of these results it can be concluded that BMP10 acts in an autocrine and paracrine fashion. As expression and localization of BMP10 changes dramatically even when the pathological changes are still moderate, BMP10 may play an important role in the disease process of dilated and hypertrophic cardiomyopathy. In cardiomyopathic hearts ventricular BMP10pos. cells seem to originate from cardiac Sca1 progenitors and it might be concluded that BMP10 induces their proliferation and differentiation. In addition, cell culture experiments show that BMP10 induced differentiation of mesenchymal cells to endothelial, smooth muscle cells and pericytes leading to the assembly of tube-like structures. BMP10 may play a protective role in the cardiomyopathies studied here by stimulating the development of the cardiac microvasculature including capillaries, arterioles and small arteries. This process might result in an inhibition or at least a delay of adverse remodeling of the heart, which is part of an important adaptive process to cardiac diseases.

BMP10 ist ein herzspezifisches Mitglied der TGF beta-Superfamilie. Im gesunden Herzen ist die Expression dieses Zytokins auf das rechte Atrium begrenzt. Die vorliegende Arbeit hatte zum Ziel die biologische Funktion von BMP10 im adulten Herzen unter physiologischen und pathologischen Bedingungen zu untersuchen. ERGEBNISSE: 1. Während der embryonalen kardialen Entwicklung konnte die Bmp10 Expression im trabekulierten Myokard detektiert werden. Das BMP10 Protein wurde außerdem im Ausflusstrakt, der kompaktierten Herzwand und im Epikard nachgewiesen. 2. BMP10 wird im gesunden adulten Herzen im rechten Atrium exprimiert. Nach der Sekretion bindet das Protein an die Membranen beider atrialen Kardiomyozyten und die interstitialen Zellen. Des Weiteren wurden die Expression und die Bindung des Proteins in den Trikuspidalklappen und den benachbarten Zellen der Arterien in der oberen atrialen Region des Herzen beobachtet. 3. Die murinen Modelle, die in dieser Studie verwendet wurden, repräsentieren eine dilative und eine hypertrophe Form der Kardiomyopathie. Sie weisen verschiedene Grade der kardialen Dysfunktion auf, die durch Veränderungen im myokardialen Volumen und eine reduzierte Ejektionsfraktion charakterisiert sind. Interstitiale und reparative Fibrose, kardiomyozytäre Hyperthrophie, Fehlanordnung der Herzmuskelfasern und Zelltod in Bezug auf Apoptose und Nekrose konnte in allen Modellen festgestellt werden. Die Anzahl der apoptotischen und nekrotischen Zellen in den untersuchten Modellen war gering. 4. In den geschädigten Herzen konnten zwei Typen einer qualitativen Veränderung der BMP10 Verteilung gefunden werden. Zum einen war die subzelluläre Lokalisation von BMP10 im rechten Atrium verändert, und zum anderen wurde BMP10 in ventrikulären Zellen reexprimiert. 5. In der Desmin ko und in Doxorubizin induzierten dilativen Kardiomyopathien konnte eine Hochregulation der BMP10 Expression gefunden werden, während die Quantifizierung von BMP10 in MnSOD +/- und Isoproterenol behandelten Mäusenherzen eine verringerte Expression aufdeckte. Da die Anzahl der BMP10pos Zellen in den Ventrikeln der pathologischen Herzen gering ist, repräsentieren die quantitativen Veränderungen höchstwahrscheinlich die Deregulierung der BMP10 Expression im rechten Atrium. 6. Ventrikuläre Zellen, die ektopisch BMP10 im pathologischen Herz exprimieren, sind Sca1pos und weisen Anzeichen der Proliferation auf. Die Charakterisierung dieser BMP10pos Zellen enthüllte, dass sie eine heterogene Population von Zellen darstellen, die oftmals endotheliale Marker und solcher glatter Muskulatur exprimieren, aber niemals Kardiomyozyten-spezifische Gene. Dennoch wird BMP10 von embryonalen und atrialen Kardiomyozyten exprimiert. 7. Die BMP10-Effekte sind abhängig von differentiell exprimierten Rezeptoren in den verschiedenen Zelllinien. Im Gegensatz dazu induziert BMP10 in multipotenten mesenchymalen 10T1/2 Fibroblasten, adulten Knochenmark abstammenden mesenchymalen Stammzellen und in nicht-Kardiomyozyten, die aus dem adulten Mausherzen isoliert wurden, endotheliale, perikardiale und für glatte Muskulatur typische Marker. Darüber hinaus sind die Zellen, die diese Marker exprimieren, in der Lage, dreideimensionale röhrenartige Strukturen zu bilden. Dies weist auf eine mögliche Rolle von BMP10 während der Angiogenese hin. SCHLUSSFOLGERUNGEN: Basierend auf den dargestellten Ergebnissen kann postuliert werden, dass BMP10 auf eine autokrine und parakrine Art und Weise wirkt. Da die BMP10 Expression und Lokalisation sich dramatisch verändert, auch wenn die pathologischen Veränderungen noch moderat sind, ist es möglich, dass BMP10 eine wichtige Rolle im Krankheitsverlauf der dilativen und hypertrophen Kardiomyopathien spielt. In kardiomyopathischen Herzen könnten die ventrikulären BMP10pos Zellen möglicherweise aus kardialen Sca1pos Vorläufern hervorgehen, deren Proliferation und Differenzierung durch BMP10 induziert wird. Des Weitern zeigten die Zellkulturexperimente, dass BMP10 die Differenzierung von mesenchymalen Zellen zu endothelialen Zellen, Zellen der glatten Muskulatur und Perizyten induziert, was schließlich zur Bildung von röhrenähnlichen Strukturen führt. In den untersuchten Kardiomyopathien könnte BMP10 eine protektive Rolle spielen, indem es die Entwicklung der kardialen Mikrovaskulatur inklusive der Kapillaren, Arteriolen und kleinen Atrierien stimuliert. Dieser Prozess resultiert möglicherweise in einer Inhibition oder zumindest einer Verzögerung der nachteiligen Umgestaltung des Herzens.
Funktionale Auswirkungen der BMP10 Expression in pathologischen Herzen
Keywords: Cardiomyopathies; BMP10; TGF beta; Sca1; mesenchymal stem cells; Kardiomyopathien; BMP10; TGF beta; Sca1; mesenchymalen stam Zellen; ddc:610